Culture in vitro of human pituitary gland adenoma and study on the production of growth hormore - ΣΤΟΦΟΡΟΣ Ε.; ΜΠΑΤΡΙΝΟΣ Μ.; ΠΙΤΟΥΛΗΣ Σ.; ΜΕΝΕΓΑΤΟΣ Ι.; ΜΑΣΤΡΟΓΙΑΝΝΗ Μ.; ΖΩΛΟΥ Α.; ΑΞΙΩΤΗΣ Ι. (Journal of the Hellenic Veterinary Medical Society, 2019)
The Authors present the result of a case of culture in vitro of Human Pituitary gland adenoma by the application of the organ and monolayer tissue culture. It is also presented that the above mentioned cells is possible to product growth hormone continiously up to a certain quantity (units).